种三明治结构石墨烯基金属或金属氧化物的快速制备方法 (2018)
本发明涉及种三明治结构石墨烯基金属或金属氧化物的快速制备方法。所述三明治结构石墨烯基金属或金属氧化物的制备方法包括以下步骤：分别制备氧化石墨烯和金属氨基络合物溶液；将金属氨基络合物溶液滴加到石墨烯溶液中，产生沉淀；收集沉淀，在惰性气体保护下高温加热；得到具有三明治结构的石墨烯基金属或金属氧化物。该方法制备的石墨烯基金属或金属氧化物复合物具有以下优势：制备方法简单快速，可以大量制备石墨烯基金属或金属氧化物复合物，复合物具有三明治结构，金属或金属氧化物颗粒具有纳米尺寸，金属或金属氧化物颗粒高度分散于石墨烯层间。因此，该复合物具有优异的电化学性能，可用作锂电池和超级电容器的电极材料。 The invention relates to a quick preparation method for graphene base metal or metal oxide with a sandwich structure. The preparation method for graphene base metal or metal oxide with the sandwich structure comprises the following steps of: preparing oxidized graphene and metal ammine complex solutions separately; dropwise adding the metal ammine complex solution into the graphene solution to generate sediments; collecting the sediments and performing high-temperature heating under the protection of an inert gas; and obtaining graphene base metal or metal oxide with the sandwich structure. A graphene base metal or metal oxide compound prepared with the method has the following advantages: the preparation method is simple